2020
DOI: 10.3390/ijerph17103346
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Psychological Well-Being among Swedish Audit Firm Employees

Abstract: The attractiveness of audit firms as employers appears to have decreased in recent years and the audit profession is currently experiencing high employee turnover. A shortage of personnel increases the risk of long-term stress and illness. This paper therefore proposes audit firm employees’ well-being as an important research topic and explores the antecedents of well-being of Swedish audit firm employees in comparison with those of other business professionals. Based on a nationwide survey of members of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To reduce potential confounding effects, several variables commonly thought to correlate with job-related wellbeing were controlled for both steps of the study. The personal characteristics were measured by a region variable (0 = rural, 1 = urban) [ 22 ], a gender variable (0 = female, 1 = male) [ 22 , 25 ], an age group variable (1 = 20 or below, 2 = 21–30, 3 = 31–40, 4 = above 40) [ 22 ], marital status (0 = unmarried, 1 = married) [ 22 ], education (1 = college or below, 2 = bachelor, 3 = master, 4 = doctor) [ 3 , 23 ], working hours per week (1 = 20 h or below, 2 = 21–40 h, 3 = 41–60 h, 4 = 61–80 h, 5 = above 80 h) [ 3 , 24 , 29 ], annual income (1 = RMB 10,000 or below, 2 = RMB 10,001–50,000, 3 = RMB 50,001–100,000, 4 = RMB 100,001–150,000, 5 = RMB 150,000 or above) [ 22 , 25 , 29 ], and industry variables which are consist of 9 type of industries, including civil service(reference group in the first step), farming/mining(0 = no, 1 = yes), manufacturing(dummy variable 0 = no, 1 = yes in the first step, reference group in the second step), power supply/construction/geological exploration/hydraulic management(0 = no, 1 = yes), transportation and network(0 = no, 1 = yes), whole/retail/restaurant(0 = no, 1 = yes), real state/finance(0 = no, 1 = yes), science/education/arts/health/media/social service(0 = no, 1 = yes), and others(0 = no, 1 = yes) [ 23 , 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce potential confounding effects, several variables commonly thought to correlate with job-related wellbeing were controlled for both steps of the study. The personal characteristics were measured by a region variable (0 = rural, 1 = urban) [ 22 ], a gender variable (0 = female, 1 = male) [ 22 , 25 ], an age group variable (1 = 20 or below, 2 = 21–30, 3 = 31–40, 4 = above 40) [ 22 ], marital status (0 = unmarried, 1 = married) [ 22 ], education (1 = college or below, 2 = bachelor, 3 = master, 4 = doctor) [ 3 , 23 ], working hours per week (1 = 20 h or below, 2 = 21–40 h, 3 = 41–60 h, 4 = 61–80 h, 5 = above 80 h) [ 3 , 24 , 29 ], annual income (1 = RMB 10,000 or below, 2 = RMB 10,001–50,000, 3 = RMB 50,001–100,000, 4 = RMB 100,001–150,000, 5 = RMB 150,000 or above) [ 22 , 25 , 29 ], and industry variables which are consist of 9 type of industries, including civil service(reference group in the first step), farming/mining(0 = no, 1 = yes), manufacturing(dummy variable 0 = no, 1 = yes in the first step, reference group in the second step), power supply/construction/geological exploration/hydraulic management(0 = no, 1 = yes), transportation and network(0 = no, 1 = yes), whole/retail/restaurant(0 = no, 1 = yes), real state/finance(0 = no, 1 = yes), science/education/arts/health/media/social service(0 = no, 1 = yes), and others(0 = no, 1 = yes) [ 23 , 24 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The classic “Easterlin paradox” also shows a complex relationship between income and wellbeing and reminds us that different regions could influence the relationship aforementioned through different economic characters [ 22 ]. Work which has always been considered a pivotal aspect of life, affect wellbeing from working time and industry by the trade-off between leisure and time spent to work [ 23 , 24 ]. The gender difference in wellbeing results from the gender gap in life expectation, which may be influenced by education [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of physical attractiveness leads to satisfaction with body image, and such body satisfaction affects emotional and psychological well-being as a prerequisite for life satisfaction. [10][11][12]. A study of healthy individuals over the age of 50 in Spain found that perceived physical attraction had a strong relationship with life satisfaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction is the vital precursor of psychological well-being and mental health [11]. Moreover, lower life satisfaction is associated with a higher mortality rate of cardiovascular disease, healthcare service utilization, and costs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Young people who enter the profession appreciate other aspects, such as expert learning, security, or meaningful work [72,73]. However, the remuneration is low among the junior professionals of the audit firms, compared to other professional services, and a lower level of well-being is observed [74]. These authors consider that the remuneration at the first stages is not competitive compared to other business professionals.…”
mentioning
confidence: 99%